CHARACTERIZATION OF SOME ALGERIANS AND FOREIGN LENTIL ACCESSIONS BY QUALITATIVE TRAITS - MERIEM LAOUAR, DJOUHER GAAD,; GABOUN, FATIMA; ABDELGUERFI, AISSA (Horticultural Biotechnology Research, 2018)
In the present study an attempt has been made to characterize lentil accessions based on qualitative traits. There were variations among 44 lentil accessions. Erect growth habit was observed in 24 % of the accessions where 8% were from Algeria. Conversely, prostrate growth habit was observed in 34% of the accessions. The majority of the remaining accessions (41.32%) were intermediate. Stem with anthocyanin pigmentation was showed in 44% of the accessions, whereas, 56% had no pigmentation (green stem). About half of the accessions had grey green leaves (53%) and 23% of accessions were light green. Among the characters, flower color showed the highest variation. White flowers were observed in 64% accessions and violet flowers were found in 36% accessions. Flowers, with violet stripes in the standard petal (SVE) were observed in 44% accessions and the majority (56%) lacked violet stripes. Yellow cotyledons were observed in 61% accessions, while the rest (39%) had red cotyledons. The majority of accessions (81%) were observed with brown testa while 14% were green and 5% had yellow testa. Absence of seed coat pattern was observed in 69% accessions. However, 8% accessions with spots, 5% with dots, 16% were marbled and the remaining 2% were complex. Flattened seed shape was observed in 60% of accessions. Conversely, globose shape was observed in 40% of the accessions, among of them 27% were from Algeria.